METAPHORICAL RESONANCE: GURU DUTT’S CINEMATIC INTERPRETATION OF ‘KAAGAZ KE PHOOL’ AND ITS PARALLEL WITH ‘DEVDAS’ - Mishra, Rashi (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The paper aims to identify and analyze the metaphorical parallels between ‘Kaagaz Ke Phool’ and ‘Devdas,’ exploring Guru Dutt’s cinematic techniques and their contribution to this resonance. Existing literature on Guru Dutt’s filmmaking style and narrative techniques provides valuable insights, yet a research gap exists regarding the specific metaphorical connection between the two works. By contextualiing both narratives within the socio-cultural landscape of post-independence India, the paper highlights their lasting relevance and societal critiques. The paper examines how ‘Kaagaz Ke Phool’ reexamines the ‘Devdas’ narrative, emphasizing the emotional complexities of the protagonists and their struggles against social norms. Through meticulous film analysis, including the study of cinematic techniques and metaphorical elements such as the rain sequences, shouting pack-up, reflection, film studio setting, and the non-linear story-telling technique, the paper uncovers the subtle parallels between the two stories. The paper underscores the lasting significance of both narratives and their contributions to the cinematic landscape, while also revealing Guru Dutt’s innovative approach.